DIMENSIONS OF MEDIA POLICY IN SATELLITE CHANNELS DIRECTED FROM THE POINT OF VIEW OF MASS COMMUNICATOR - Falhi Hammood, Ahmed; Rashid Al-Azzawi, Hussein (ALBAHITH ALALAMI, 2021)
This research was conducted in order to monitor and measure the dimensions of media policy in satellite channels directed from the point of view of the communicator, and this research is classified among the descriptive studies, as the researcher used the survey method to answer the questions that were formulated in light of the research problem represented by the main question: What are the dimensions of media policy in Directed satellite channels? . To achieve the objectives of the study, the researcher used the following tools: The questionnaire, in order to survey the attitudes of communicators about the extent to which the media policy during crises reflects on their professional standards. The research community is represented in the international satellite channels speaking the Arabic language and destined for the Arab region. As for the research sample, the researcher chose the intentional sample method on two levels. The first level: they are directed satellite channels licensed to operate in Iraq only, as there are seven directed channels. As for the second level: they are those in charge of communicating with satellite channels working in Iraq only, their number reached (55) respondents. One of the most important findings of the research was that the satellite channels directed clearly depend on the dimensions of the media policy through their adoption of the considerations of the legislative dimension, through that the most important forms imposed by the media policy in the satellite channels directed on the communicators is the category of commitment to (censorship laws) that outperformed all other categories. The research also showed that the majority of the respondents confirmed that the media policy of directed satellite channels constantly seeks to achieve the technological dimension through keeping pace with modern technology. This is evident from the keenness of the media policy of directed satellite channels in general to investigate the latest technological developments in the field of media